THE EFFECT OF PRICE, PRODUCT, AND FLASH SALE ON REPURCHASE DECISION WITH CUSTOMER SATISFACTION AS MODERATION ON TIKTOKSHOP FEATURES - Riska Atqiyya Baroroh; Kussudyarsana Kussudyarsana; Soeptaini Soeptaini (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The development of the internet from year to year continues to increase, this makes the growth of e-commerce businesses appear, one of which is Tiktokshop. This study aims to analyze the effect of price, product, and flash sales to repurchase decisions with consumer satisfaction as a variable moderating Tiktokshop. The research technique used is quantitative, data collection uses a questionnaire method and the sample in this study amounted to 100 people. The analysis in this study was assisted using SPSS and SmartPLS. The result is Price has a significant effect on repurchase decisions, product quality has a significant effect on repurchase decisions, a flash sale has a significant effect on purchasing decisions, and customer satisfaction has a significant effect on repurchase decisions. Customer satisfaction does not moderate the effect of price on repurchase decisions, customer satisfaction does not moderate the effect of product quality on repurchase decisions, and customer satisfaction moderates the effect of promotions on consumer repurchase decisions at Tiktokshop.